The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/md20010048
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gelatinase from Marine Flocculibacter collagenilyticus SM1988: Characterization and Potential Application in Collagen Oligopeptide-Rich Hydrolysate Preparation

Abstract: Although the S8 family in the MEROPS database contains many peptidases, only a few S8 peptidases have been applied in the preparation of bioactive oligopeptides. Bovine bone collagen is a good source for preparing collagen oligopeptides, but has been so far rarely applied in collagen peptide preparation. Here, we characterized a novel S8 gelatinase, Aa2_1884, from marine bacterium Flocculibacter collagenilyticus SM1988T, and evaluated its potential application in the preparation of collagen oligopeptides from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This result is in agreement with previous studies, which showed that Gly, Pro, and Hyp are abundant in collagen hydrolysates. 37,38 In the hydrolysate, the molecular weights of 62.48% of peptides were less than 1000 Da, and 30.36% less than 500 Da (Table 4 and Figure S3). For comparison, the oligopeptide contents reported in the collagen hydrolysates prepared with other proteases are shown in Table 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This result is in agreement with previous studies, which showed that Gly, Pro, and Hyp are abundant in collagen hydrolysates. 37,38 In the hydrolysate, the molecular weights of 62.48% of peptides were less than 1000 Da, and 30.36% less than 500 Da (Table 4 and Figure S3). For comparison, the oligopeptide contents reported in the collagen hydrolysates prepared with other proteases are shown in Table 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With the majority of active serine hydrolases identified from our screen being annotated as subtilases (peptidase family S8) or penicillin acylases (peptidase family S15; Tab.1–2), we indeed detected thermostable representatives of the functionally highly diverse family of serine hydrolases that already find application for industrial purposes. In particular, proteases from the subtilisin family are utilized in the laundry industry 60 or for the production of valuable chemicals from proteinaceous substrates 61,62 , whereas penicillin acylases are important enzymes for the production of 6-aminopenicillanic acid (6-APA), the β-lactam nucleus used in the manufacturing process of semi-synthetic antibiotics, through hydrolysis of natural penicillins 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results show that our eABPP approach enabled the identification of functionally diverse serine hydrolases, ranging from various proteases to esterases/lipases up to serine hydrolases with uncharacterized functions (e.g., DUFs or UPFs), thus being superior over a simple bioinformatic metagenome annotation procedure. Of note, the majority of the identified active serine hydrolases are annotated as subtilases or penicillin acylases, which demonstrates that the applied eABPP screen indeed allows the detection of thermostable representatives of the functionally highly diverse family of serine hydrolases that already find application for industrial purposes [66][67][68][69].…”
Section: Identification Of Active Serine Hydrolases By Eabppmentioning
confidence: 92%